Construction of Insulin 18‐mer Nanoassemblies Driven by Coordination to Iron(II) and Zinc(II) Ions at Distinct Sites. Issue 7 (14th January 2016) - Munch, Henrik K.; Nygaard, Jesper; Christensen, Niels Johan; Engelbrekt, Christian; Østergaard, Mads; Porsgaard, Trine; Hoeg‐Jensen, Thomas; Zhang, Jingdong; Arleth, Lise; Thulstrup, Peter W.; Jensen, Knud J.
Abstract: Controlled self‐assembly (SA) of proteins offers the possibility to tune their properties or to create new materials. Herein, we present the synthesis of a modified human insulin (HI) with two distinct metal‐ion binding sites, one native, the other abiotic, enabling hierarchical SA through coordination with two different metal ions. Selective attachment of an abiotic 2, 2′‐bipyridine (bipy) ligand to HI, yielding HI–bipy, enabled Zn II ‐binding hexamers to SA into trimers of hexamers, [[HI–bipy]6 ]3, driven by octahedral coordination to a Fe II  ion. The structures were studied in solution by small‐angle X‐ray scattering and on surfaces with AFM. The abiotic metal ligand had a higher affinity for Fe II than Zn II  ions, enabling control of the hexamer formation with Zn II and the formation of trimers of hexamers with Fe II  ions. This precise control of protein SA to give oligomers of oligomers provides nanoscale structures with potential applications in nanomedicine. Abstract : Careful planning : Well‐defined insulin 18‐mer nanoassemblies formed by metal‐ion‐mediated self‐assembly (SA) of a modified human insulin molecule (HI) have been synthesized. Attachment of an abiotic 2, 2′‐bipyridine ligand (red oval) to each HI (black triangle) enabled Zn II ‐binding hexamers to SA into trimers of hexamers driven by coordination to a Fe II  ion. Zn II =green sphere; Fe II =blue sphere.